Effect of drainage and wildfire on peat hydrophysical properties. Issue 13 (19th April 2013) - Sherwood, J. H.; Kettridge, N.; Thompson, D. K.; Morris, P. J.; Silins, U.; Waddington, J. M.; Carey, Sean; Buttle, Jim
Abstract Consecutive multiple disturbances to northern peatlands can dramatically impact peat hydrophysical properties. We examine the impact of a double disturbance (drainage and wildfire) on the hydrophysical and moisture retention properties of peat, a key regulator of peatland ecohydrological resilience, and compare this with the impact to each individual disturbance (drainage and wildfire). The compound effect of drainage and wildfire resulted in a shift of the surface datum down the peat profile, revealing denser peat. Less‐dense near‐surface peats that regulate water‐table position and near‐surface moisture content, both favourable to Sphagnum recolonization, were lost. At a drained peatland that was then subject to wildfire, peat bulk density increased by 14.1%, von Post humification class increased by two categories and water retention increased by 15.6%, compared with an adjacent burned but undrained (single disturbance) portion of the fen. We discuss the key hydrophysical metrics of peatland vulnerability and outline how they are affected by the isolated impacts of drainage and wildfire, as well as their combined effects. We demonstrate that multiple peatland disturbances have likely led to an increase in hydrological limitations to Sphagnum recovery, which may impact peatland ecohydrological resilience. Copyright © 2013 John Wiley & Sons, Ltd.